2020
DOI: 10.1371/journal.pone.0234612
|View full text |Cite
|
Sign up to set email alerts
|

Work honored by Nobel prizes clusters heavily in a few scientific fields

Abstract: We aimed to assess whether Nobel prizes (widely considered the most prestigious award in science) are clustering in work done in a few specific disciplines. We mapped the key Nobel prize-related publication of each laureate awarded the Nobel Prize in Medicine, Physics, and Chemistry (1995-2017). These key papers mapped in only narrow sub-regions of a 91,726-cluster map of science created from 63 million Scopus-indexed published items. For each key Nobel paper, a median of 435 (range 0 to 88383) other Scopus-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…To check the relationship between SB–PR pairs and other impact indicators, we examine 133 key papers related to Nobel Prize-winning findings selected by (Ioannidis et al. 2020 ) within the dataset. The analysis reveals that there are seven SBs and six PRs in Prize-winning papers.…”
Section: Resultsmentioning
confidence: 99%
“…To check the relationship between SB–PR pairs and other impact indicators, we examine 133 key papers related to Nobel Prize-winning findings selected by (Ioannidis et al. 2020 ) within the dataset. The analysis reveals that there are seven SBs and six PRs in Prize-winning papers.…”
Section: Resultsmentioning
confidence: 99%
“…Second, recent work on the GSE concluded that the business of predicting the next Nobel had become a fruitless exercise since the laureates rank among the 500 most-cited authors after the 1970s compared to those awarded in the early twentieth century and their contributions have been limited to research niches rather than the discipline as a whole [ 22 ]. This was further refined by Ioannidis et al [ 7 ], who found that of the 114 domains investigated, only five (i.e., particle physics [14%], cell biology [12.1%], atomic physics [10.9%], neuroscience [10.1%], and molecular chemistry [5.3%]) accounted for 52.4% of the Nobel Prizes awarded. Taking a closer look at the features of the Nobelists’ papers, Zhou et al [ 54 ] estimated that 74.7% were cited more than 500 times, innovative research was more cited than theoretical and experimental methods, and most of the papers were published in journals with an Impact Factor between 5–10.…”
Section: Literature Reviewmentioning
confidence: 97%
“…Despite the considerable research already undertaken, the above literature review exposes two major limitations. First, as noted by Zheng and Liu [ 18 ] and Ioannidis et al [ 7 ], further studies are needed that will incorporate other disciplines such as the social sciences and humanities. Second, since the study by Schlagberger et al [ 33 ] focused solely on US institutions, a broader landscape is needed to research institutions in developing countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…By regressing the number of scientific prizes won by each winner on a set of variables, the authors found that the propensity of winning scientific prizes could be explained by a person’s university prestige, high h -index, and by the fact that they belonged to a prize-winning genealogical network. In a separate but related study [ 42 ], investigated if papers associated with Nobel Prizes in physics, medicine or chemistry between 1995 and 2017 were heavily clustered only in a handful disciplines. They found that only 5 out 114 fields of science accounted for more than half of the studied Nobel Prizes.…”
Section: Related Workmentioning
confidence: 99%